Arsenic and fifteen other metal (loid)s exposure of children living around old mines in the south of France - Igor Pujalté; Zeno Loi; Alice Bernard; Lionel Moulis; Sophie Delpoux; Jacques Gardon (Ecotoxicology and Environmental Safety)
As many countries plan to resume mining for the energy transition, assessing the health impacts of past activities is crucial. This cross-sectional study investigated whether children living near four old mines in southern France were exposed to higher levels of arsenic and 15 other metal(loid)s compared to those in unexposed areas. Arsenic, a prevalent contaminant, was used as an indicator to explore exposure in relation to children's lifestyles (housing, activities, diet) and their environments (soil, dust, water). The study included 240 children—138 from exposed areas and 102 from control areas. Urine samples were analyzed for inorganic arsenic, its metabolites, and other trace elements. No significant difference was found in average age, BMI, or parental education between groups. Urinary arsenic levels were similar for children living near mines and those in control areas (6.4 vs. 7.0 µg/g; p = 0.152). Proximity to mining sites did not increase arsenic exposure (r Pearson = 0.142). Instead, factors like age, seafood consumption, and environmental conditions were more influential. Children who ate seafood had higher arsenic levels in urine (p < 0.001). In a subgroup near mines, arsenic in soil and dust was significantly linked to increased exposure (p < 0.001). Overall, metal exposure levels were comparable to or lower than national averages. Access to clean water, mine closures, and health awareness likely kept exposure low. Ongoing biomonitoring is crucial for identifying and mitigating health risks in communities living near former mining areas.